Desain Aplikasi Pemesanan Online untuk Meningkatkan Pelayanan di Selvas Catering Sleman Yogyakarta - Agus Sujarwadi; Muhammad Fadhli Annazhif; Dibyo Susilo; Surya Darmawan; Sujoko (Jurnal ABDI RAKYAT, 2024)
The catering business produces food and beverages for sale to consumers with the goal of maximizing profits. The numerous catering businesses in the Special Region of Yogyakarta, both large and newly established, increase competition in aspects such as ordering methods and marketing media. Therefore, a system that utilizes the internet to market catering services is needed to help business owners more easily market and manage order data. Currently, the buying and selling process in catering businesses still uses conventional methods in marketing and transaction management, which have several inefficiencies. This community service aims to design an online catering ordering application to help business owners implement this design into an application that can be used to manage order data and market their business more broadly